DAMPAK PERBEDAAN AKSES TEKNOLOGI TERHADAP KESENJANGAN SOSIAL EKONOMI (The Impact of Differences in Technology Access on Socio-Economic Inequalities) - Nur Afifah Azzahra; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
In this modern era, access to technology is increasingly developing rapidly which can provide positive and negative values ​​in various aspects, especially economic and social aspects. This difference in access to technology causes increasingly widespread socio-economic disruption. This research aims to analyze the impact of differences in technology access on socio-economic disparities and identify factors that influence this access, such as geographic, educational and economic factors. The research method used is a qualitative research method and data collection techniques originating from journals. The results of this research show what impact differences in access to technology have on the social disparities that occur and show that groups of people who have access to technology find it easier to develop economic and social capabilities through educational courage, remote work opportunities, and participation in digital economic activities. On the other hand, people who do not have access to technology or digital skills experience limitations in improving their quality of life and are at risk of experiencing social isolation. In addition, this gap in technology access brings together inequality in income and participation in the political process, which deepens the gap in social inequality. This research suggests the importance of policy interventions from governments and social institutions to provide digital skills training programs and expand technological infrastructure in remote areas. With this approach, equal access to technology is expected to reduce socio-economic disparities and encourage more inclusive social development.